Migration and remittances in Kazakhstan: First evidence from a household survey - Barbara Dietz; Kseniia Gatskova; Achim Schmillen (Osteuropa-Institut Regensburg, 2011)
Internal migration flows in Kazakhstan are of high social and political relevance but political and public attention has primarily been devoted to external movements. This paper presents the main descriptive results of a new household survey on migration and remittances in Kazakhstan which was conducted in four cities (Almaty, Astana, Karaganda and Pavlodar) between October and December 2010. It summarizes the survey's methodology, gives an overview over the basic characteristics of respondents, illustrates migration experiences on the individual and the household level and compares migrants and non-migrants. Furthermore, the prevalence of remittances and attitudes towards migration are discussed.
Keywords: C81; F24; R23; 330; Kazakhstan; data analysis; regional migration; remittances; Binnenwanderung; Rücküberweisung (Migranten); Privater Haushalt; Kasachstan